The identification of cultural tourism geographies: results from a systematic literature review - Palermo, Annunziata; Chieffallo, Lucia; Virgilio, Sara (Geographica Pannonica, 2023)
Tourism development allows the enhancement of the heritage of local cultural resources, expressing the territorial potential. The Systematic Literature Review shown in this paper highlight the relationship between “cultural heritage” and “tourism”. The current state of the art and the specific relationships between the contents of the selected publications demonstrate that tourism is an indispensable tool in local communication and cultural promotion policies and strategies. The qualitative results allow the identification of cultural tourism geographies that coincide with four thematic clusters not evident in advance.